Building customer relationships in Indian financial services - Puthenpurakkal, Sambhunath (2011)
Relationship Marketing is the strategy used by the companies to establish, maintain and enhance long term relationship with the customers. This study is aimed to understand the customer perceptions on the market orientation of private and public sector banks in India and to identify the factors that contribute to the formation of strong and close customer relationships. Based on the literature review, four factors such as trust, commitment, satisfaction and communication are found to be the strong drivers of customer retention. The commitment is considered as a multidimensional construct for this study consisting of affective commitment, behavioural commitment and continuance commitment. The empirical data for measuring the constructs is collected from banking customers across India. According to the results, all factors showed a positive correlation to customer retention except behavioural commitment. The study also found a statistically significant difference in the behavioural commitment and communication of private and public sector banks.